The importance of process in modern tectono-stratigraphy and regional geology - Lunt, Peter; Luan, Xiwu (Berita Sedimentologi, 2024)
In its simplest form geology is a history, which appears to only require the compilation of a chronicle. However, our data is fragmentary, and aspects such as the dimension of time and the depositional setting of sediments are obscured, especially the correlation of time over wide areas and determining rates of change. As a result, geology cannot advance just by accumulating observations, expecting that a credible narrative will inevitably emerge. There must be reality checks on the proposed history to avoid confirmation bias towards over-simple expectations. In a region suspected to be complicated and, in many ways, unique we require an abductive investigative technique to reconstruct its history. This means to force testing through cross-checking independent but related data types. Such inter-disciplinary testing can produce a rigorous framework, even to reconstruct special situations not accommodated by ideas models. This essay examines three topics necessary for such evidence-based investigation. The first is to investigate and document the reliability of observations (like the “error-bars” required in hard-sciences). Secondly is the shift from model-based to evidence-based processes (from deductive to abductive reasoning). Thirdly is the need to consider if conclusions are “significant” - i.e., is there confidence that an interpretation would be repeatable by independent workers, as well as being distinct from background variability in data. It is proposed that we must acknowledge the replication crisis highlighted in the past two decades in other sciences by considering how we work in the complex geology of SE Asia, to prevent a similar validation crisis undermining the value of the science here.